2011
DOI: 10.1186/1756-0500-4-216
|View full text |Cite
|
Sign up to set email alerts
|

Dengue epidemic in Malaysia: Not a predominantly urban disease anymore

Abstract: BackgroundDengue infection has been an important and serious public health concern in Malaysia ever since its first reported case here in 1902. Nevertheless, to our knowledge, no nationwide investigation has been carried out to determine the actual magnitude of dengue endemicity in the Malaysian population. In this study, we describe a cross sectional seroepidemiology study of dengue IgG seroprevalence in the Malaysian adult population.FindingsFrom 1000 subjects (35-74 years old), 91.6% subjects were found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 15 publications
(18 reference statements)
6
45
1
Order By: Relevance
“…In 1999, cases of CHIK infection were reported at the Javanese city [16]. Results from the Yogjakarta and our studies imply that, although CHIK infections seemed comparatively lower in prevalence compared to dengue in Southeast Asia (such as 91.6% in Malaysia and 45% in Singapore among the adult population and 65.7% among the school children in Vietnam), sporadic outbreaks with high attack rates could still occur in this region [17-19]. Taking it all together, routine CHIK surveillance and vector control should be given due consideration in Southeast Asia and regions having tropical/sub-tropical weather that promotes the spread of CHIK vectors, to minimize and prevent the occurrence of outbreaks.…”
Section: Discussionmentioning
confidence: 89%
“…In 1999, cases of CHIK infection were reported at the Javanese city [16]. Results from the Yogjakarta and our studies imply that, although CHIK infections seemed comparatively lower in prevalence compared to dengue in Southeast Asia (such as 91.6% in Malaysia and 45% in Singapore among the adult population and 65.7% among the school children in Vietnam), sporadic outbreaks with high attack rates could still occur in this region [17-19]. Taking it all together, routine CHIK surveillance and vector control should be given due consideration in Southeast Asia and regions having tropical/sub-tropical weather that promotes the spread of CHIK vectors, to minimize and prevent the occurrence of outbreaks.…”
Section: Discussionmentioning
confidence: 89%
“…Over the past decades however, changes have been observed in the age-distribution of DHF cases in most countries both in Southeast Asia and Latin America [1317]. Nowadays it is reported that a significant proportion of DHF cases occur among adolescent and adult patients in Southeast Asia [15, 1719], and also in Latin American countries [20]. However, many studies describing shifting age patterns of DHF fail to report continuous observations over longer periods of time or report on specific locations and outbreaks [1417].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of dengue shows an increasing trend from 44.3 cases/100,000 population in 1999 to 181 cases/100,000 population in 2007 [3]. High dengue IgG seropositivity (>91%) was found in a sample of Malaysian adults aged 35 to 74 years old in a recent study [4]. Serological tests conducted in Lundu District in Sarawak, Malaysia, found that in >23% of 215 samples, individuals had a history of dengue [5].…”
Section: Introductionmentioning
confidence: 99%